أثر استيعاب القواعد النحوية والمفردات على قدرة الترجمة لدى طلبة الجامعة الإسلامية الحكومية قدس - Azwar Annas (UIN Fatmawati Sukarno Bengkulu, 2019)
This study sought to determine the influence of grammar and vocabularies mastery on the students ability of translate in the Kudus Islamic University. The approach articles used in this study is a quantitative approach because researchers wanted to test the hypothesis that shaped assosiative hypothesis (is the hypothesis that asks a relationship between two or more variables). This approach is said to be a quantitative approach because the existing data in the form of numbers and statistics used in analyzing it. Meanwhile, the method used is research Correlation, because the correlation study researchers wanted to uncover the relationship of variations in the correlation coefficient. The results of this research are: 1) the effect of gramatikan mastery to capability students of translate in the Kudus Islamic University as 0.4925 rhitung score greater than 0.317 rtabel. This shows a significant correlation while the coefficient of determination between X1 and Y of 24.25303%. 2) the effect of vocabulary mastery to capability students of translate in the Kudus Islamic University as a score of 0.605 rhitung greater than 0.317 rtabel. This shows a significant relationship coefficient of determination between X2 and Y amounted to 36.62499%, 3) The calculation Ry.X1X2 0.589, ryx1 0.492 and 0.605 ryx2 greater than 0.317 rtabel. This shows that there is a relationship multi positive correlation between mastery of vocabulary and grammatical to capability students of translate in the Kudus Islamic University and acceptance of the hypothesis.